Ruta metodológica para la caracterización de las creencias epistemológicas de profesores del distrito en torno a las pedagogías críticas en ELT (Memorias Sifored - Encuentros Educación UAN, 2022)
Critical pedagogies have been widely addressed in the academic community due to their contribution to the construction of critical citizenships. However, there is little research and academic production in the training of English teachers and their teaching practices. This paper shows the methodological route for the characterization of the epistemological beliefs of the district's English teachers in relation to critical pedagogy. This research exercise is developed in two phases: 1. A quantitative characterization of the teachers' beliefs and their teaching practices; and 2. A focus group for the reflection on critical pedagogies in ELT. It is considered important to understand the contribution that critical pedagogies represent to the teaching of English, the training and qualification of English teachers, a field in which this proposal aims to contribute.
Keywords: Challenges of Post-pandemic education; critical pedagogy; ELT (English Language Teaching); teacher training; teachers’ epistemological beliefs